The Impact of Diversity Management and Leadership on Performance in Maritime Industry: Array - Keceli, Yavuz; Zaim, Halil; Kum, Serdar; Dinc, Muhammet Sait; Momin, Mujtaba (EuroEconomica, 2020)
Many shipping companies hire crew members from different nationalities and cultural backgrounds due to several reasons such as cost reduction and the unavailability of national seamen. Shipping companies also face major problems when managing a diverse group of crew members on-board like cultural differences and communication problems. These problems are reported to have an impact on the company’s overall performance. Therefore, this study tries to investigate the impact of diversity management policies and leadership on shipping companies’ performance. A questionnaire survey has been conducted on shipping professionals working in Turkish companies. The model of the study was tested using structural equation modelling. The results indicate that diverse policies and strong leadership can improve a company’s performance by raising personal and organizational awareness in the company.